2013
DOI: 10.1002/ange.201305669
|View full text |Cite
|
Sign up to set email alerts
|

Generation of HNO and HSNO from Nitrite by Heme‐Iron‐Catalyzed Metabolism with H2S

Abstract: Nitrite has been shown in the past decade to be an important source of nitric oxide that acts as a vasodilator and intrinsic signaling molecule. [1] Numerous studies have proved that nitrite can be reduced in vivo, either non-enzymatically [2a,b] or enzymatically, in reactions catalyzed by xanthine oxidase, [2c] deoxyhaemoglobin, [2d] deoxymyoglobin, [2e] cytochrome c, [2f] or by thiol and metal-center-assisted processes inside the cell. [2g] The mechanism of the last process has recently been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
(31 reference statements)
1
39
0
2
Order By: Relevance
“…In addition, Pálinkás et al (2014) have recently investigated interactions of H 2 S with human myeloperoxidase (MPO), a major contributor to inflammatory oxidative stress, to show that H 2 S inhibits the enzyme by reducing iron centre and by binding to the reduced Fe 2+ . It is still, however, unclear to which extent is the coordination and/or reduction of metal centres involved in signalling by H 2 S. Miljkovic et al (2013) demonstrated that metal centres in mitochondria are responsible for the H 2 S-stimulated haem centre-catalysed reduction of nitrite, a reaction which can explain the use of nitrite as an antidote for acute H 2 S poisoning.…”
Section: Reactions With Metal Centresmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, Pálinkás et al (2014) have recently investigated interactions of H 2 S with human myeloperoxidase (MPO), a major contributor to inflammatory oxidative stress, to show that H 2 S inhibits the enzyme by reducing iron centre and by binding to the reduced Fe 2+ . It is still, however, unclear to which extent is the coordination and/or reduction of metal centres involved in signalling by H 2 S. Miljkovic et al (2013) demonstrated that metal centres in mitochondria are responsible for the H 2 S-stimulated haem centre-catalysed reduction of nitrite, a reaction which can explain the use of nitrite as an antidote for acute H 2 S poisoning.…”
Section: Reactions With Metal Centresmentioning
confidence: 98%
“…3f). Namely, some iron haem centres are able to oxidize hydrogen sulfide forming HS• (Miljkovic et al 2013), which could in turn react with free thiols to finally generate protein persulfides (Zhang et al 2014). Cytochrome c, for example, readily reacts with H 2 S (Wedmann et al 2014).…”
Section: Reaction With Metal Centres and Generation Of Hs•mentioning
confidence: 99%
“…Myoglobin (Mb) heme appears to be key to hypoxic vasodilation, as it is present in rat aortic smooth muscle and in Mb null rats (Mb -y-) hypoxic vasodilation is impaired (170). Recently, Miljkovic et al (106) showed that H 2 S is a rapid mediator of nitrite reduction by providing reducing equivalents to Fe 3 + , thereby generating both NO and its reduced congener, nitroxyl (HNO). Vasodilation produced by acute hypoxia in mice in vivo appears to be independent of NO production, and it is associated with reduced plasma nitrite concentration and increased RSNOs (174).…”
Section: Hsno/snomentioning
confidence: 99%
“…Reduction of the iron forms a nitrosyl-Fe 2 + that then binds an additional H 2 S which results in the liberation of thionitrus acid (HSNO) and this can also give rise to H 2 S, polysulfide (HSSH), NO and its reduced congener, nitroxyl (HNO), and protein Snitrosothiol (RSNO), all of which could contribute to vascular signaling. Modified from Miljkovic et al (106).…”
Section: Physiological Evidence For H 2 S-mediated O 2 Sensingmentioning
confidence: 99%